Stagnation point flow of a water-based graphene-oxide over a stretching/shrinking sheet under an induced magnetic field with homogeneous-heterogeneous chemical reaction - Zaib, Aurang; Khan, Umair; Ishak, Anuar; Waini, Iskandar; Pop, Ioan; Elattar, Samia; M. Abed, Ahmed (Elsevier B.V., 2023)
Water has received a great deal of attention as lubrication for production due to its efficiency, affordable, and friendly to the environment. GO (graphene oxide) ingredients have the capability to upsurge the efficiency of water lubrication owing to theire extraordinary machine-driven/mechanical properties, water dispensability, and variety of practical uses. With such a motivation, it is anticipated the effect of the induced magnetic field (IMF) on the fluid flow close to a standstill point created by a stretching/shrinking sheet with a homogeneous-heterogeneous chemical reaction and dispensed with water-based GO nanoparticles. The leading governing partial differential equations (PDEs) of the problem are converted into ordinary differential equations (ODEs) via employing similarity variables. After that, the resulting equations are worked out numerically with help of the bvp4c (boundary-value problem of fourth-order) solver. Figures are employed as representations to demonstrate the stimulation of pertinent parameters such as the reciprocal magnetic parameter, the magnetic parameter, the Prandtl number, the Schmidt number, the ratio of the diffusion coefficients, radiation, nanoparticle volume fraction, heat source/sink, and heterogeneous reaction parameter on the profile of induced magnetic, velocity, temperature, concentration, rate of heat transfer, and friction factor. It is noted that both the gradients are enhanced by the nanoparticle fraction volume. Moreover, dual solutions can be established in the limited values of stretching/shrinking parameter. Moreover, the shear stress upsurges by almost 4.18% and 0.52% for the upper and lower solution branches with higher values of the solid nanoparticles volume fraction, respectively, whilst it shrinkages up to 7.56% in the upper branch outcome owing to the higher influence of the magnetic parameter but increases by almost 14.56% for the lower branch solution.